How to eat in space - Taylor, Helen Springhetti; Lewis, Stevie (Little, Brown and Company, 2023)
This fact-filled look at the sometimes complicated task of eating while away from Earth will show young readers what it's really like to live on the space station, with engaging back matter that takes a deep dive into the topic and features photos of real NASA astronauts!
Keywords: syöminen; astronautit; avaruusasemat; avaruus